2014
DOI: 10.1074/jbc.m114.565069
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Control of MIN6 Pancreatic β Cells Is Enhanced by Impaired Amino Acid Signaling

Abstract: Background: Depletion of the GPCR T1R1/T1R3 increased calcium and ERK1/2 signaling by carbachol. Results: T1R3 depletion or reducing amino acids overnight increased M3 muscarinic receptor expression and altered calcium responses. Conclusion: M3 receptor expression in ␤ cells is up-regulated by reduced amino acid availability. Significance: The M3 muscarinic receptor is a potential therapeutic target in ␤ cells with impaired amino acid sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Pilocarpine Stimulates ERK Phosphorylation in MIN6 Cells with a Bias toward the Src-Mediated Pathway. Like other GPCRs, M3R is known to activate extracellular signal-regulated kinases, ERK1/2 (Luo et al, 2008;Selway et al, 2012;Guerra et al, 2014). Activation of ERK can occur via distinct mechanisms that can involve G protein-and b-arrestin-mediated pathways and result in ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Pilocarpine Stimulates ERK Phosphorylation in MIN6 Cells with a Bias toward the Src-Mediated Pathway. Like other GPCRs, M3R is known to activate extracellular signal-regulated kinases, ERK1/2 (Luo et al, 2008;Selway et al, 2012;Guerra et al, 2014). Activation of ERK can occur via distinct mechanisms that can involve G protein-and b-arrestin-mediated pathways and result in ERK phosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…A study from 1997 indicated that the ERK1/2 signal transduction pathway is not required for GSIS [13]. However, it has been demonstrated that, in MIN6 mouse pancreatic b-cells and primary rat islet b cells, blocking the ERK1/2 signaling pathway can reduce GSIS [14,15]. In this study, we found that IL-1b can inhibit ERK1/2 activation under glucose stimulation in bTC-6 cells, and the effect of inhibition is related to IL-1b concentration.…”
Section: Discussionmentioning
confidence: 99%
“…A study from 1997 indicated that the ERK1/2 signal transduction pathway is not required for glucose-stimulated insulin secretion (15). However, it has been demonstrated that is found that in MIN6 mouse pancreatic β-cells and primary rat islet β cells, blocking of the ERK1/2 signaling pathway reduced glucose-stimulated insulin secretion (14,16). Furthermore, Vlacich et al (17) reported that the protein kinase Pim3 can inhibit the activation of the ERK1/2 signal pathway through suppressor of cytokine-induced signaling 6 and regulates glucose-stimulated insulin secretion.…”
Section: Discussionmentioning
confidence: 99%